A randomized control study on the effect of probiotics on feed tolerance in very low birth weight neonates - Senthil Kumaran G; Chairman Muthu Prem Kumar L; Jeyarama Krishnan R (Asian Journal of Medical Sciences, 2024)
Background: Probiotics are live microbial supplements that increase feed tolerance, colonize the gut of these newborns with beneficial flora, and promote growth in these infants. Aims and Objectives: This study was planned to compare the role of probiotics in low birth weight (LBW) infants in the time taken to reach full feeds, episodes of feed intolerance, weight gain, duration of hospital stay, incidence of necrotizing enterocolitis (NEC) stage 2 or more, and morbidity and mortality during hospital stay. Materials and Methods: This interventional two-arm blinded randomized control study was conducted in Thoothukudi Government Medical College Hospital, Thoothukudi, from November 2019 to October 2020. The selected sample of babies was randomly divided into two groups, the probiotic and the no-probiotic group. Bifidobacterium breve M-16 was administered to infants in the probiotic group at a dose of 0.5 g/day once a day in breast milk. Only breast milk was used to feed babies in the no-probiotic group. Results: The time to reach full enteral feed was shorter in the probiotic group (9.21±1.74 days) than in the no-probiotic group (12.43±3.74 days). Better feed tolerance (12%) was seen in the probiotic group than in the no-probiotic (44%) group. A low incidence of sepsis (12%) was seen in the probiotic group than in the non-probiotic group (40%). A lesser duration of hospital stay (10.42±1.77 days) was seen in the probiotic group than in the probiotic group (13.78±4.18 days). Conclusion: Very LBW neonates who received probiotic supplements along with their feeds have shorter times to reach full feeds, greater feed tolerance, lower rates of sepsis, and shorter mean hospital stays.